Critiquer les sciences et la médecine dans un pays non hégémonique - Mathieu Quet (Revue d'anthropologie des connaissances)
The years 1960 and 1970 in many industrialized countries, are times of a large dissent movement on scientific and technological development. Controversies (pesticides, nuclear energy, asbestos) multiply and some groups are questioning radically against science and technology, in favour of alternative practices considered to be more democratic. These groups (Science for the People in the United States, Impascience in France) have been abundantly documented. Their history is less known in non hegemonic countries. Our study focuses on movements of critique of science in India, in particular on the critique of medicine. We show a certain specificity vis-à-vis European and American movements. Whereas in industrialized countries a clear cut exists between the positivist critique of science (of communist influence) and the radical critique (more influenced by leftist movements), in India a more nuanced distinction appears and both these two strands are mixed together. This complexity is shown in a study on the status of indigenous knowledge in the critique of medicine, in particular on the question of the relation of traditional knowledge and techno-scientific knowledge.